CONQUER ANYTHING : A GREEN BERET'S GUIDE TO BUILDING YOUR A-TEAM - Stube, Greg; Miniter, Frank (New York : Post Hill Press, 2019)
A narrative investigation into the generic drug boom draws on exclusive accounts and extensive confidential FDA documents to expose life-threatening practices of global fraud, data manipulation, and unsafe medicine production.
Includes bibliographical references (pages 243-281) and index.
Keywords: Stube, Greg; United States. -- Army -- Special Forces; Self-actualization (Psychology); Mental discipline; Conduct of life; Mothers -- Psychology; Feminism